MUSLIM DIGITAL MARKET FACEBOOK SEBAGAI MEDIA PROMOSI DAKWAH MELALUI KALIGRAFI - Fauziah, Rahmah El; Fatoni, Uwes (PAI RAFAH, 2024)
The development of technology and the times force humans to adapt, including in preaching. Although new communication technology (da'wah transmission) cannot completely replace old technology, it can allow old technology to take on a new role. This causes moving with the times in the corridor of Islam so that it can develop in accordance with the methods of da'wah transmission, which includes the use of Facebook social media as a tool to promote da'wah through calligraphy, so this study reveals several things about the utilization of Facebook and cutting elements of da'wah based on the title "Utilization of Facebook as a Means of Da'wah Through Calligraphy". Using a descriptive approach, this research describes and analyzes ideas by using data collection techniques through in-depth interviews with resource persons, namely the founders and collaborators of the calligraphy community in Padang, West Sumatra, "Kaligrafi Sakato". From the results of this study, it was found that Facebook is seen as an effective means of preaching through verses of the Qur'an and the Prophet's Sunnah that are beautifully written by the recipients of calligraphy services, namely the Sakato calligraphy community